2013
DOI: 10.1038/nature12208
|View full text |Cite
|
Sign up to set email alerts
|

A single pair of interneurons commands the Drosophila feeding motor program

Abstract: Summary Many feeding behaviors represent stereotyped, organized sequences of motor patterns that have been the subject of neuroethological studies1,2 such as electrophysiological characterization of neurons governing prey capture in toads1,3. Technical limitations, however, have prevented detailed study of the functional role of these neurons as in other studies on vertebrate organisms. Complexities involved in studies of whole animal behavior can be resolved in Drosophila, where remote activation of brain cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
198
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(205 citation statements)
references
References 41 publications
(69 reference statements)
7
198
0
Order By: Relevance
“…Recently one group reported that a single pair of NP883-Gal4 labeled neurons acts as interneurons and directs the feeding motor program [55]. They named this pair of neurons "Fdg neurons" and showed that these neurons are essential for normal feeding behavior through activation and ablation experiments [55]. Their results are consistent with ours in that activation of these neurons triggers PER and food ingestion.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Recently one group reported that a single pair of NP883-Gal4 labeled neurons acts as interneurons and directs the feeding motor program [55]. They named this pair of neurons "Fdg neurons" and showed that these neurons are essential for normal feeding behavior through activation and ablation experiments [55]. Their results are consistent with ours in that activation of these neurons triggers PER and food ingestion.…”
Section: Discussionsupporting
confidence: 81%
“…In recent years, although much progress has been made in identifying first-order sensory neurons and motor neurons controlling feeding movement, a direct connection between the two neuronal populations has not been reported, which suggests that there is at least a one-step relay mediated by interneurons in the SOG [31,32]. Recently one group reported that a single pair of NP883-Gal4 labeled neurons acts as interneurons and directs the feeding motor program [55]. They named this pair of neurons "Fdg neurons" and showed that these neurons are essential for normal feeding behavior through activation and ablation experiments [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified additional neurons in the SOG whose activity depends on starvation: tyrosine hydroxylase ventral unpaired medial (TH-VUM) dopaminergic neurons that modulate feeding in response to nutritional needs (Marella et al, 2012) and feeding (Fdg) interneurons that integrate gustatory input with the internal state to command a feeding behavior routine (Flood et al, 2013). However, neither the TH-VUM nor Fdg neurons are likely to make direct connections with sweet taste neurons.…”
Section: Discussionmentioning
confidence: 98%
“…First, the gustatory neuropil of the SOG, which includes the subesophageal zone (SEZ), gnathal ganglia (GNG), and parts of the periesophageal neuropil (Ito et al, 2014), is relatively disorganized compared with the olfactory and visual neuropils, therefore posing a challenge for anatomical identification of gustatory circuits. Second, although it is possible that the SOG encompasses some local circuits that connect sensory, motor, and command neurons that have processes in this region (Flood et al, 2013;Gordon and Scott, 2009;Melcher and Pankratz, 2005;Rajashekhar and Singh, 1994), it is apparent that taste information must also be conveyed to higher brain centers, including the mushroom body, which contains neurons activated upon sucrose ingestion (Liu et al, 2012). However, even the location of the secondary taste relay remains a mystery because projection neurons that synapse with taste sensory neurons have not yet been identified.…”
Section: Introductionmentioning
confidence: 97%
“…The 337-nm nitrogen laser unit (337-USAS; Micro Point) was calibrated and adjusted as previously described (24). The laser lesion was performed using a previously published protocol with slight modification (6,53). SI Materials and Methods gives more details.…”
Section: Methodsmentioning
confidence: 99%